Analisis Faktor-Faktor Yang Mempengaruh Pergantian Kantor Akuntan Publik Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia( Periode 2011-2014 ) - Prastyo, Faisal Luthfi Yulian, Dra. Rina Trisnawati, Ak, Msi, Ph.D (2016)
Substitution Public Accounting Firm (KAP)ofthe company in the Indonesia Stock Exchange (BEI) can occur because of a conflict interest between the company (client) with KAP interests, or the interests of one party are not met. there are several factors that may trigger the turn of KAP as the turn of the new management, the company is experiencing financial disstred, want to replace with a larger accounting firm, etc.. The purpose of this study was to determine the effect of management changes, reputation of auditors, financial difficulties,going concern opinion, and size of the client to turn KAP in manufacturing companies. This research is empirical research using secondary data from the annual report. The population is all manufacturing companies listed in Indonesia Stock Exchange (BEI) from 2011-2014. dataCollecting using purposive sampling method and acquired 33 companies as research samples. Data were analyzed using logistic regression analysis, feasibility test of the model, the model fit,coefficient of determination, classification matrix models and wald test. The results of this study indicate that the going concern opinion variables have an influence on the turn of a public accounting firm in Indonesia. While the other variables such as management changes, the reputation of auditors, financial difficulties do not affect the change of public accounting firms in Indonesia.